2008
DOI: 10.1149/1.2806173
|View full text |Cite|
|
Sign up to set email alerts
|

Role of Surfactant Molecules in Post-CMP Cleaning

Abstract: In order to understand the effects of surfactant molecules on post-chemical mechanical planarization ͑CMP͒ cleaning, we used a tribology setup to simulate the cleaning process. An anionic surfactant ͑alcohol ether sulfates͒ was used during cleaning. Effects of surfactant concentration ͑below and above its critical micelles concentration͒ and temperature on cleaning were experimentally tested. Results showed that increase in surfactant concentration ͑over 0.75 wt %͒ can promote bilayer interaction of micelles o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(14 citation statements)
references
References 19 publications
0
14
0
Order By: Relevance
“…Furthermore, triton X-100 is well known for its superior surface cleaning action and has been widely used in post-CMP cleaning solutions. 5,29,30 While triton X-100 by itself is incapable of breaking any of the relevant bonds here, it can assist the other components in the solution to access sub-100 nm particles and facilitate their removal. 26,27 Triton X-100 can coat the particles and reduce adhesion between them and the film surface, making it easier for them to be lifted away.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, triton X-100 is well known for its superior surface cleaning action and has been widely used in post-CMP cleaning solutions. 5,29,30 While triton X-100 by itself is incapable of breaking any of the relevant bonds here, it can assist the other components in the solution to access sub-100 nm particles and facilitate their removal. 26,27 Triton X-100 can coat the particles and reduce adhesion between them and the film surface, making it easier for them to be lifted away.…”
Section: Resultsmentioning
confidence: 99%
“…The wafer surfaces, post-CMP, are typically cleaned using suitable cleaning solutions in conjunction with poly vinyl alcohol (PVA) brush scrubbing and/or megasonics. [3][4][5] For example, Tseng et al 6 polished patterned STI wafers with a commercial ceria slurry and cleaned them using DI water or 2-10 wt% H 2 O 2 in a megasonic tank and a basic cleaning solution having a pH value of 10.5 in brush stations 1 and 2 for 14 nm STI and poly-open CMP (POC) process. They found that the particle contamination levels were higher on nitride surface than on oxide surface.…”
mentioning
confidence: 99%
“…e cleaning is not effective due to fewer micelle formation in the cleaning solution as it is superconcentrated. Fewer micelles and foaming in the cleaning solution are not beneficial in the cleaning application [28].…”
Section: Model For Critical Micelle Concentrationmentioning
confidence: 99%
“…However, critical micelle concentrations for these surfactants from the literature are far less than 10 mg/mL [76]. In the use of surfactants as the cleaning media combined use of surfactants and mechanical removal might be necessary to fully overcome the adherence of NMs to substrates [110,112].…”
Section: Chemical Cleaningmentioning
confidence: 99%